International Day of Action (IDoA) Against Contract Cheating 2020—Update from the chair of the IDoA planning committee (Canadian Perspectives on Academic Integrity, 2020)
The International Day of Action (IDoA) Against Contract Cheating occurred October 21st 2020 and coincided with the Carnegie Council’s Global Ethics Day. This year over 250 organizations registered for the event from around the world. While speaking up and out against contract cheating remained a main theme for the day, there was also a keen interest to inspire and promote international connections. Active student involvement and an ambitious 20 hours of live feed were just two of the accomplishments for the day. Canadian voices were also present leading up to and during the day.